Control of cortical neuronal migration by glutamate and GABA - Luhmann, Heiko J.; Fukuda, A.; Kilb, W. (Frontiers in Cellular Neuroscience, 2015)
Neuronal migration in the cortex is controlled by the paracrine action of the classical neurotransmitters glutamate and GABA. Glutamate controls radial migration of pyramidal neurons by acting primarily on NMDA receptors and regulates tangential migration of inhibitory interneurons by activating non-NMDA and NMDA receptors. GABA, acting on ionotropic GABAA-rho and GABAA receptors, has a dichotomic action on radially migrating neurons by acting as a GO signal in lower layers and as a STOP signal in upper cortical plate (CP), respectively. Metabotropic GABAB receptors promote radial migration into the CP and tangential migration of interneurons. Besides GABA, the endogenous GABAergic agonist taurine is a relevant agonist controlling radial migration. To a smaller extent glycine receptor activation can also influence radial and tangential migration. Activation of glutamate and GABA receptors causes increases in intracellular Ca2+ transients, which promote neuronal migration by acting on the cytoskeleton. Pharmacological or genetic manipulation of glutamate or GABA receptors during early corticogenesis induce heterotopic cell clusters in upper layers and loss of cortical lamination, i.e. neuronal migration disorders which can be associated with neurological or neuropsychiatric diseases. The pivotal role of NMDA and ionotropic GABA receptors in cortical neuronal migration is of major clinical relevance, since a number of drugs acting on these receptors (e.g. anti-epileptics, anesthetics, alcohol) may disturb the normal migration pattern when present during early corticogenesis.